Lekcja języka obcego z uczniem niepełnosprawnym miejscem badań metodą indywidualnych przypadków - Burzyńska, Małgorzata (Neofilolog, 2010)
The article presents preliminary results of research conducted during English language classes, with the case study method, among pupils with intellectual disability attending a primary special needs school. The research was meant to help answer the questions related to the possibility of incorporating foreign language teaching in the comprehensive process of their rehabilitation, and especially the development of individual cognitive skills as well as the mother tongue command. The article emphasizes the advantages of research based on a case study which enables the researcher to apply the principle of individualization and the treatment of every pupil as a subject no matter what the developmental barriers may be.